The Stimulative Effect of Yangjing Capsule on Testosterone Synthesis through Nur77 Pathway in Leydig Cells - Gu, Yalong (Evid Based Complement Alternat Med, 2015)
Yangjing Capsule (YC), an innovative Chinese medicine based on traditional prescription, promotes testosterone synthesis by upregulating the expression of steroidogenic enzymes. Nur77 as a nuclear receptor is known to regulate the expression of many steroid synthetases. This study aimed to explore the potential mechanisms by which YC regulates testosterone synthesis in Leydig cells. Real-time PCR and Western blot analysis were employed to assess the expressions of steroidogenic enzymes and Nur77 after treating MLTC-1 cells with YC. The luciferase reporter gene assay was performed to detect the activity of Nur77 gene promoter. Also, the expressions of steroid synthases were detected after Nur77 gene was knocked down. YC significantly stimulated Nur77 production and upregulated StAR and HSD3B expression, and this agrees with the activity of Nur77 gene promoter that was significantly enhanced by YC. Interestingly, knockdown of Nur77 blocked the above YC's effects and consequently inhibited testosterone synthesis in MLTC-1 cells. YC promotes StAR and HSD3B expression and upregulates testosterone synthesis in Leydig cells, which is mediated by Nur77 pathway.